Generation of bovine cytotoxic cell lines, specific for cells infected with the protozoan parasite Theileria parva and restricted by products of the major histocompatibility complex - Goddeeris, Bruno M.; Morrison, W. Ivan; Teale, A.J. (Wiley, 1986)
Cytotoxic cell lines specific for cells infected with the protozoan parasite Theileria parva were generated in vitro by repeated stimulation of peripheral blood mononuclear cells (PBMC) from immune animals with autologous parasitized cells from continuously growing cell lines. In PBMC of 5/7 immune animals tested, maximal levels of killing (80–100%) were obtained at effector to target ratios of 10/1 following 3 to 5 stimulations. No killing of uninfected lymphoblasts was observed. Cytotoxic activity was contained in the BoT4− lymphocyte population. The results of analyses of cytotoxicity on panels of target cells of diverse major histocompatibility (MHC) phenotypes indicated that the effectors were restricted by class I MHC antigens. Only autologous targets and allogenic targets sharing one or other bovine lymphocyte antigen A locus‐encoded specificity with the cytotoxic cell line were killed. In addition, two of the three cytotoxic cell lines, when tested on targets infected with different parasite stocks, exhibited a high degree of specificity for the stock used for immunization and stimulation of the cultures. The capacity to generate highly cytotoxic, MHC‐restricted effectors from peripheral blood was dependent on the immune status of the donor animals. This was confirmed by comparing cytotoxicity generated from the same animal before and after immunization using the same autologous infected cell line as a stimulator. These results indicate that these effector cells are analogous to the cytotoxic cells detected in vivo in cattle undergoing immunization or challenge with T. parva.